Integration of Traditional Islamic Jurisprudence and Modern Human Rights Norms: Toward a Harmonious Shari’a Framework - Nopiana Mozin; Jamaludin Jamaludin; Najamudin Najamudin (International Forum of Researchers and Lecturers, 2024)
The relationship between traditional Islamic jurisprudence (fiqh) and modern international human rights norms has long been characterized by debate and tension. Islamic law is commonly perceived as divinely grounded and normatively authoritative, whereas human rights frameworks are often viewed as secular, universal, and rooted in modern legal philosophy. This perceived dichotomy has contributed to the widespread assumption that Sharī‘a and human rights are inherently incompatible, particularly in sensitive areas such as gender equality, freedom of religion, and minority rights. Reassessing this tension is especially important for Muslim-majority societies that must reconcile religious legitimacy with global human rights obligations. This study explores the potential for harmonizing classical Islamic jurisprudence with contemporary human rights norms by identifying shared values, points of divergence, and feasible pathways for integration. Using a qualitative normative legal approach, the research employs doctrinal analysis of primary Islamic legal sources alongside international human rights instruments, supported by comparative analysis of key rights, including the protection of life, religious freedom, and gender equality. Interpretative analysis is applied to examine how classical and contemporary Islamic scholars conceptualize human rights within the Sharī‘a framework. The findings reveal substantial convergence between Islamic law and human rights norms, particularly in their shared emphasis on human dignity, justice, equality, and social welfare. While interpretative tensions persist, they are largely shaped by contextual and institutional factors rather than by the core ethical objectives of Islamic law. Integrative approaches grounded in ijtihad, maṣlaḥa, and maqāṣid al-sharī‘a offer constructive pathways for harmonization.